1999
DOI: 10.1161/01.atv.19.9.2179
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Oxidation Products Induce Vascular Foam Cell Lesion Formation in Hypercholesterolemic New Zealand White Rabbits

Abstract: Abstract-Circulating cholesterol oxidation products (ChOx) have long been implicated in the etiology of early atherosclerosis; however, direct in vivo evidence elucidating their role in atherogenesis is only recently becoming available. This study investigated ChOx effects on vascular lesion formation in New Zealand White rabbits under controlled hypercholesterolemic conditions. By closely monitoring plasma cholesterol levels and adjusting dietary cholesterol intake during a 78-day period, total plasma cholest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 76 publications
3
19
0
Order By: Relevance
“…In the present study, we used a 7-Kchol concentration of 40 g/ml, which is ϳ25-fold higher than levels found in human plasma after a fat-rich meal. However, this concentration is compatible with the high levels of oxidized lipids accumulated in advanced human atherosclerotic plaque and is close to the levels found in the plasma of (19) and cholesterol-fed rabbits (41). The constitutively active Nox proteins, which produce low levels of ROS under basal conditions, can be upregulated in the vascular wall by proinflammatory factors, such as growth factors and cytokines (16,47).…”
Section: Discussionsupporting
confidence: 58%
“…In the present study, we used a 7-Kchol concentration of 40 g/ml, which is ϳ25-fold higher than levels found in human plasma after a fat-rich meal. However, this concentration is compatible with the high levels of oxidized lipids accumulated in advanced human atherosclerotic plaque and is close to the levels found in the plasma of (19) and cholesterol-fed rabbits (41). The constitutively active Nox proteins, which produce low levels of ROS under basal conditions, can be upregulated in the vascular wall by proinflammatory factors, such as growth factors and cytokines (16,47).…”
Section: Discussionsupporting
confidence: 58%
“…48 We recently reported that injection of oxysterols 49 increased the amount of oxysterol deposition in the aortic wall and when combined with cholesterol feeding also increased the deposition of cholesterol and fatty streak formation. 50 Oxysterol content in the aortic arch and abdominal aorta increased; however, the amount of oxysterols and extent of cholesterol deposition was much lower in the abdominal aorta. These differences indicate that factors such as shear force or humoral responses may influence the extent of oxidative stress, promoting the formation of lipid peroxidation products in areas of predilection.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, the formation of foam cells as a consequence of phagocytes from the macrophage-oxidized LDL has also been detected, with the retention of cholesterol in the vascular wall and the activation of ACAT (acetyl-cholesterol-acyl-transferase) [5], this point being key to the role of macrophages in the progression or regression of the lesions [4].…”
Section: Rabbitsmentioning
confidence: 99%
“…Both participate in the adhesion and extravasation of the monocytes into the subendothelial space, where they are transformed into macrophages. These subendothelial macrophages participate in transforming the LDL into highly oxidized LDL (oxLDL), which after being taken up by the macrophages contributes to the formation of foam cells [5] such as those seen in the large cho-roidal vessels and in the suprachoroid of hypercholesterolaemic rabbits [6]. The saturation of the foam cells leads to their death and the release of toxic products such as esterified and oxidized cholesterol, a scenario that inflicts greater endothelial damage and encourages the progression of the atherosclerotic lesion.…”
Section: Introductionmentioning
confidence: 99%